Student Perceptions of Artificial Intelligence as a Virtual Tutor and Its Relation to Self-Efficacy in Learning - Muhammad Auwal Yakubu; Zohaib Hassan Sain; Uthman Shehu Lawal; Mohamad Arif Rahman Hakim (Indonesian Journal of Progressive Pedagogy, 2025)
This study investigates the use of Artificial Intelligence (AI) as a virtual tutor and its impact on students' self-efficacy in learning. Interviews, observations, and documentation from 30-40 students across various disciplines were analyzed using a mixed-methods approach. Findings show that AI enhances students' self-efficacy by providing quick, personalized feedback, boosting confidence in completing academic tasks. However, students reported challenges with complex topics requiring human-like explanations. Key factors influencing perceptions of AI included ease of use and technological comfort, which positively correlated with the perceived effectiveness of AI as a tutor. The study highlights the potential of AI to support learning but emphasizes the need for a balance with human interaction, especially for more complex subjects. This research contributes to understanding AI’s role in education. It offers insights for enhancing AI integration, recommending further development and training programs to improve students' digital literacy and engagement with AI systems